Sex-specific associations with cerebrospinal fluid biomarkers in dementia with Lewy bodies - M. van de Beek (Alzheimer’s Research & Therapy, 2020)
Abstract Background Dementia with Lewy bodies (DLB) is more prevalent in men than in women. In addition, post-mortem studies found sex differences in underlying pathology. It remains unclear whether these differences are also present antemortem in in vivo biomarkers, and whether sex differences translate to variability in clinical manifestation. The objective of this study was to evaluate sex differences in cerebrospinal fluid (CSF) biomarker concentrations (i.e., alpha-synuclein (α-syn), amyloid β1-42 (Aβ42), total tau (Tau), phosphorylated tau at threonine 181 (pTau)) and clinical characteristics in DLB. Methods We included 223 DLB patients from the Amsterdam Dementia Cohort, of which 39 were women (17%, age 70 ± 6, MMSE 21 ± 6) and 184 men (83%, age 68 ± 7, MMSE 23 ± 4). Sex differences in CSF biomarker concentrations (i.e., α-syn, Aβ42, Tau, and pTau) were evaluated using age-corrected general linear models (GLM). In addition, we analyzed sex differences in core clinical features (i.e., visual hallucinations, parkinsonism, cognitive fluctuations, and REM sleep behavior disorder (RBD) and cognitive test scores using age- and education-adjusted GLM. Results Women had lower CSF α-syn levels (F 1429 ± 164 vs M 1831 ± 60, p = 0.02) and CSF Aβ42 levels (F 712 ± 39 vs M 821 ± 18, p = 0.01) compared to men. There were no sex differences for (p) Tau concentrations (p > 0.05). Clinically, women were older, had a shorter duration of complaints (F 2 ± 1 vs M 4 ± 3, p < 0.001), more frequent hallucinations (58% vs 38%, p = 0.02), and scored lower on MMSE and a fluency task (MMSE, p = 0.02; animal fluency, p = 0.006). Men and women did not differ on fluctuations, RBD, parkinsonism, or other cognitive tests. Conclusions Women had lower Aβ42 and α-syn levels than men, alongside a shorter duration of complaints. Moreover, at the time of diagnosis, women had lower cognitive test scores and more frequent hallucinations. Based on our findings, one could hypothesize that women have a more aggressive disease course in DLB compared to men. Future research should investigate whether women and men with DLB might benefit from sex-specific treatment strategies.